Metabonomics reveals that triclocarban affects liver metabolism by affecting glucose metabolism, β-oxidation of fatty acids, and the TCA cycle in male mice. (15th December 2018) - Li, Wentao; Zhang, Wenpeng; Chang, Mengyang; Ren, Juan; Xie, Wenping; Chen, Huiming; Zhang, Zhenqing; Zhuang, Xiaomei; Shen, Guolin; Li, Haishan
Graphical abstract: Highlights: TCC inhibited aerobic glycolysis of glucose in the live. TCC increased anaerobic glycolysis and gluconeogenesis. TCC accelerated the β-oxidation of fatty acids and TCA cycle. Short-term TCC exposure could affect liver metabolism. Abstract: This study combined metabonomics with molecular biology techniques to identify differential endogenous substances produced by triclocarban (TCC) that affect plasma and liver metabolism in mice, to map their associated metabolic pathways, and to systematically determine the mechanism of TCC affecting liver metabolism in mice. The results showed that TCC affected liver metabolism by a mechanism involving the inhibition of glucose oxidation in the liver, promotion of anaerobic glycolysis and gluconeogenesis, and accelerated β-oxidation of liver fatty acids and the TCA cycle, which lead to metabolic disorders of the liver microenvironment in mice. The analysis of endogenous substances in the liver and plasma indicated that TCC caused physiological and pathological changes in the liver, and affected the physiological state of mice and the metabolic balance of endogenous substances. Based on metabonomics and bioinformatics analysis methods, this study elucidated a new mechanism involved in how TCC affects liver metabolism.